Systematic Review of Halal Studies Adopting Theory of Planned Behaviour - Nabila Nizar; andi triyawan (Tazkia Islamic Finance and Business Review, 2020)
Halal sector has emerged as one of the fastest growing markets in the world. Along with the increasing demand for halal products, researchers and experts have also produced a growing body of knowledge in the halal field. This paper aims to unveil the emergence and growth of halal studies using theory of planned behavior. Theory of Planned Behavior consists of three main variables: attitude toward the behavior, subjective norm, and perceived behavior. The method used is a systematic literature review, following Barbara Khitchenham. The authors found that 123 papers were qualified to be included in the study. There are 24 themes discussed in these halal studies, with the most significant contribution focused on consumption and products. Majority of studies are from Malaysia and Indonesia. Further research is necessary to examine several themes that are still not widely studied.